2018
DOI: 10.1123/apaq.2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adults With Neurologic Disability Recruited for Exercise Trials: A Secondary Analysis

Abstract: This review examined demographic and clinical characteristics of participants from exercise trials in 3 neurologic disability conditions (multiple sclerosis, spinal cord injury, and traumatic brain injury) and compared these data with population-based statistics. The authors included 75 published studies from 2006 to 2016: 53 studies for multiple sclerosis (n = 2,034), 14 for spinal cord injury (n = 302), and 8 for traumatic brain injury (n = 272). Pooled data resembled some heterogeneous aspects of population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…These concerns led to the development of a theory that may enhance recruitment strategies for PA programs. Recruitment is the current rate-limiting factor for implementing high-quality randomized controlled trials in this population [5,10] and severely attentuates external validity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These concerns led to the development of a theory that may enhance recruitment strategies for PA programs. Recruitment is the current rate-limiting factor for implementing high-quality randomized controlled trials in this population [5,10] and severely attentuates external validity.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality confirmatory evidence (i.e., randomized controlled trials and meta-analyses) can expedite the translation of carefully controlled clinical interventions into real-world community-settings, but PA studies have been consistently impeded by an inability to enroll large enough samples of people with SCI or wheelchair users to reach an adequate level of external validity [5,6]. A recent scoping review found that only 42% of adults with physical disabilities who were contacted agreed to enroll in a PA trial [10]. Common reasons for nonparticipation included unspecified refusal to participate, exclusion due to wheelchair use, difficulties with travel, unavailable transportation, and scheduling concerns [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite what is known about the positive effects of exercise in improving health and function,1 people with physical disabilities remain one of the least active and obese2–8 populations in society. In the latest data from the Centers for Disease Control and Prevention, nearly one-half of all adults with disabilities perform no aerobic physical activity 9.…”
Section: Introductionmentioning
confidence: 99%